Mutagenic effect of contaminated soil on the offspring of exposed rats - Garcia, Edariane Menestrino; Silva Junior, Flavio Manoel Rodrigues da; Muccillo-Baisch, Ana Luiza (Acta Scientiarum. Health Sciences, 2016)
This study aimed to measure irreversible DNA damage in the offspring of rats exposed to contaminated soil. Bone marrow cells were removed from the femurs of the offspring of rats that were exposed to contaminated soil via gavage during three different periods: 21 days prior to detection of pregnancy, during pregnancy and 21 days after birth, during the lactation period. For each group, we also had a control group under the same experimental conditions but exposed to uncontaminated soil. The results showed that pups borne of rats exposed to contaminated soil had an increase in the number of micronuclei in the different exposure groups compared with their respective control groups. This suggests a potential risk of mutagenic damage to the offspring of pregnant women who live at the sampling site.